Reduced juvenile long-term depression in tuberous sclerosis complex is mitigated in adults by compensatory recruitment of mGluR5 and Erk signaling. - Wyatt B Potter (Public Library of Science (PLoS), 2013)
Tuberous sclerosis complex (TSC) is a multisystem genetic disease that manifests with mental retardation, tumor formation, autism, and epilepsy. Heightened signaling through the mammalian target of rapamycin (mTOR) pathway is involved in TSC pathology, however it remains unclear how other signaling pathways are perturbed and contribute to disease symptoms. Reduced long-term depression (LTD) was recently reported in TSC mutant mice. We find that although reduced LTD is a feature of the juvenile mutant hippocampus, heightened expression of metabotropic glutamate receptor 5 and constitutively activated Erk signaling in the adult hippocampus drives wild-type levels of LTD. Increased mGluR5 and Erk results in a novel mTOR-independent LTD in CA1 hippocampus of adult mice, and contributes to the development of epileptiform bursting activity in the TSC2(+/-) CA3 region of the hippocampus. Inhibition of mGluR5 or Erk signaling restores appropriate mTOR-dependence to LTD, and significantly reduces epileptiform bursting in TSC2(+/-) hippocampal slices. We also report that adult TSC2(+/-) mice exhibit a subtle perseverative behavioral phenotype that is eliminated by mGluR5 antagonism. These findings highlight the potential of modulating the mGluR5-Erk pathway in a developmental stage-specific manner to treat TSC.